A Mathematical Model of Human Health and Longevity Based on Unified Complex Systems Theory - Weicheng Cui (European Journal of Applied Sciences, 2026)
Healthspan and lifespan are routinely conflated in traditional medicine and aging biology, while materialist reductionism neglects non‑material causal factors. Here we present a mathematical framework for human health and longevity grounded in the Unified Complex Systems Theory (UCST), featuring mind–body dualism, active–passive force dynamics, and open‑system axioms. We rigorously decouple health as the dynamic homeostatic capacity of an open system and longevity as the total duration of mind–body coupling. Integrating the 14 updated hallmarks of aging and recent population evidence, we establish a continuous‑time dynamic health index model and a probability–duration longevity model that incorporate environmental, physiological, psychological, lifestyle, and untimely death risks. Active force (a) is identified as the core shared regulator that modulates entropy, homeostasis, and survival resilience. This work fills the theoretical gap of non‑material variables in post‑materialist health science and provides a quantifiable, verifiable tool for personalized health maintenance, precision longevity intervention, and public health optimization.